Сhickenpox and complications in children in modern conditions - E. Yu. Skripchenko; I. V. Petrov; A. V. Astapova; A. V. Klimkin; N. V. Skripchenko; G. P. Ivanova; O. V. Goleva; N. V. Marchenko; A. V. Golubeva; P. S. Verbenko (Детские инфекции (Москва))
In the article, we characterize clinical manifestations of varicella-zoster infection in children. The observation of complications of acute period and period of late reconvalescence of chicken-pox is given. We give description of possible factors, which lead to complicated case of acute varicella zoster infection and further virus persistence with neurological damage.